Physical activity knowledge, attitudes and practices of the elderly in Bloemfontein old age homes - P.E. Pienaar; M. de Swardt; M. de Vries; H. Roos; G Joubert (South African Family Practice, 2004)
Background: The aim of this study was to describe physical activity knowledge, attitudes and practices of the elderly in Bloemfontein old age homes.